Diversity and Interrelations Among the Constitutive VOC Emission Blends of Four Broad-Leaved Tree Species at Seedling Stage - Fitzky, Anne Charlott; Peron, Arianna; Kaser, Lisa; Karl, Thomas; Graus, Martin; Tholen, Danny; Pesendorfer, Mario; Mahmoud, Maha; Sandén, Hans; Rewald, Boris (Frontiers in Plant Science, 2021)
Volatile organic compounds (VOCs) emitted by plants constitute for a broad range of different gases, which serve the purpose protecting against herbivores, communicating with insects and neighboring plants, or increasing the tolerance to environmental stresses. Evidence is increasing that the composition of VOC blends plays an important role in fulfilling these purposes. Constitutional emissions give insight in species-specific stress tolerance potentials and are an important first step linking metabolism and function of co-occurring VOCs. Thus, we investigate here the blend composition and interrelations among co-emitted VOCs in unstressed seedlings of four broad-leaved tree species, Quercus robur, Fagus sylvatica, Betula pendula and Carpinus betulus. As expected, VOCs of Q. robur and F. sylvatica mainly emitted isoprene and monoterpenes, respectively. B. pendula had the highest sesquiterpene emission; however, it made up only 1.7 % of its total emissions while the VOC spectrum was dominated by methanol (~72 %). C. betulus was emitting methanol and monoterpenes in similar amounts compared to other species, questioning its frequent classification as a close-to-zero VOC emitter. Beside these major VOCs, a total of 22 VOCs could be identified—with emission rates and blend compositions varying drastically between species. A principal component analysis among species revealed co-regulations between multiple compounds. In particular, new links between pathways and catabolites were indicated, as we found e.g. correlated emission rates of methanol, sesquiterpenes (mevalonate pathway), and green leaf volatiles (hexanal, hexenylacetate and hexenal; lipoxygenase pathway). Further, acetone emissions correlated with eugenol from the Shikimate pathway, a relationship that has not been described before. Our results thus indicate that certain VOCs are highly interrelated within species, pointing towards the importance to improve our understanding of VOC blends rather than targeting dominant VOCs only.